MRI in Athetotic Cerebral Palsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The MRI in 22 children with athetotic cerebral palsy was studied in the Department of Pediatric Neurology, Seirei-Mikatabara General Hospital, Hamamatsu, the Department of Pediatrics, National Rehabilitation Center for Disabled Children, Tokyo, and the Department of Pediatrics, Nagoya City University Medical School, Japan.